Childhood adversities and chronic pain among midlife employees. (13th November 2019) - Salonsalmi, A; Lallukka, T; Lahelma, E; Pietiläinen, O; Rahkonen, O
Abstract: Introduction: Chronic pain is common among employees. Childhood adversities are known determinants of adult health but their association with chronic pain in adulthood is largely unknown. We aimed to examine the associations between childhood adversities and chronic pain among midlife employees. Methods: Data on seven childhood adversities and chronic pain (pain having lasted at least 3 months) were derived from the baseline survey of the Helsinki Health Study collected in 2000 to 2002 among 40 to 60-year-old employees of the City of Helsinki in Finland. The study included 8140 employees of whom 80% were women. The analyses were made by logistic regression and the results are presented as odds ratios (OR) and their 95% confidence intervals (CI). Age, gender, father's education, own education, marital status, working conditions, sleep problems and common mental disorders were included as covariates. Results: Economic difficulties in the childhood family (OR 1.60, 95% CI 1.41-1.81), childhood illness (1.74, 1.45-2.08), parental divorce (1.26, 1.07-1.48), parental alcohol problems (1.34, 1.18-1.52) and bullying in school or among peers (1.59, 1.37-1.89) were associated with an increased odds of chronic pain in midlife. Adjusting for father's education, own education and marital status did not contribute to the associations. Working conditions, sleep problems and common mental disorders slightly attenuated the associations between childhood adversities and chronic pain. Conclusions: Childhood adversities associate to chronic pain in midlife. The results suggest that promoting well-being among children might lead to less pain decades after childhood. Key messages: Childhood adversities are associated with chronic pain in adulthood. Considering well-being among children might lead to less pain decades after childhood.